Evaluasi Genotipe Sorgum Manis (Sorghum bicolor (L.) Moench) Produksi Biomas dan Daya Ratun Tinggi - Efendi, Roy; Aqil, M.; Pabendon, Marcia B. (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
The possibility of sustainable use of sweet sorghum as raw material for animal feed and bioethanol need to be supported by evaluation and selection of sweet sorghum genotypes for high biomass production, sugar content of the stalk, and its ratooning ability. An experiment was conducted at the experimental field of the Cereal Crops Research Institute, Maros, during the anomalic season (La Nina) from November 2009 to September 2010. Fourteen genotypes of sweet sorghum were planted in plots arranged in a randomized block design with three replications. The sorghum seeds were planted as primary crop plants in November 2009 and harvested in February 2010. Ratoons of the primary crop (Ratoon I) started to grow in February 2010 and was harvested in May 2010, while Ratoon II started to grow in May 2010 and was harvested in August 2010. The results showed that none of the sorghum genotypes had the potential of high fresh biomass production, high ratooning ability, and high sugar content of stalk juice. Genotype 15021A produced the highest fresh biomass (63.4 t/ha), but had low ratooning ability l (33-44%) and low sugar stalk juice content (9 brix). Meanwhile, genotype 15105B had high ratooning ability (64-88%) and high sugar content of stalk juice (13 brix), but it had a low fresh biomass production (41.8 t/ha). The amount of fresh biomass production from the primary crop plants until Ratoon II was determined by the potential production of fresh biomass/ha and ratooning capability of the sorghum genotype. The fresh biomass production of the sorghum genotype was correlated with the plant height and the date of flowering.